(untitled) (BIRDEM Medical Journal, 2020)
Outcome of coronavirus disease 2019 (COVID-19) is worse among elderly population, those with diabetes mellitus and other co-morbidities and such patients are prone to develop multiple complications. An elderly diabetic lady got admitted for acute myocardial infarction. Subsequent evaluation revealed a positive reverse transcriptase polymerase chain reaction (RT-PCR) for severe acute respiratory syndrome coronavirus 2 (SARSCoV- 2), acute kidney injury, acute hepatitis and sepsis. She was managed accordingly and her post-discharge follow-up was satisfactory. Birdem Med J 2020; 10, COVID Supplement: 120-121